Public and Private Sector Capital Formation and Economic Growth in Malawi - Ngalawa, Harold P.E.; Kutu, Augustine Adebayo (International Journal of Economics and Financial Issues, 2024)
This paper investigates the relative importance of public and private sector capital formation on economic growth in Malawi. Employing both the Two-Stage Least Squares and dynamic Generalised Method of Moments techniques on quarterly data from 1970Q1 to 2019Q4, the study finds that private sector capital formation makes a significant contribution to economic growth. The relationship between public sector capital formation and economic growth, however, is insignificant. The study finds no evidence of complementarity between public and private sector capital formation in Malawi. The study observes that private sector capital formation affects public sector capital formation, and not vice versa. Consistent with orthodox classical political economics, we recommend a small government for Malawi with a lean budget, especially since there are no observed benefits from large government spending in spurring economic growth. The only public sector investments that may be undertaken are public goods in areas associated with market failure.